Answer:
(x -1)(12x +13)
Step-by-step explanation:
You are looking to rewrite the middle term as the sum of terms that have factors of (12)(-13) that have a total of +1. Those factors are -12 and +13, so the expression you are factoring by grouping is ...
12x^2 +13x -12x -13
= x(12x +13) -1(12x +13)
= (x -1)(12x +13)
What do you need to help?
Correct question with correct options has been attached
Answer:
37
Step-by-step explanation:
Let C represent those dressed as heroes and let B represent those wearing mask
Thus;
n(C) = 39
n(D) = 45
We are told that 21 entrants were dressed as heroes wearing a mask.
Thus; n(C n D) = 21
We are also told that there were a total of 100 entries.
Thus, n(T) = 100
Now, number of entrants neither dressed as heroes nor wearing a mask is given by;
n(T) - n(C u D)
n(C u D) = n(C) + n(D) - n(C n D)
n(C u D) = 39 + 45 - 21
n(C u D) = 63
Thus;number of entrants neither dressed as heroes nor wearing a mask is: 100 - 63 = 37
Answer:
x = 11.1
Its a right angle triangle with the values of its adjacent and hypotenuse given so cos is used.
Answer:
x=17/13
Step-by-step explanation:
-3(3x-3)=4/5(5x-10)
-9x+9=4x-8
-13x= -17
x=17/13